Nickel oxide supported cobalt catalyst and preparation method and application thereof
The catalytic conversion of furfural to furfurfural alcohol by nickel-oxide-supported cobalt catalyst under high temperature and low pressure conditions, solving the problems of high cost of existing catalysts and environmental pollution, achieving efficient and low-cost furfural conversion without hydrogen atmosphere, optimizing reaction conditions, and conversion Rate and selectivity were significantly improved.
Patent Information
- Application Number
- CN202410255029.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-06
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-03-06
AI Technical Summary
The existing catalysts have high costs in the preparation of furfurfural hydrotrene, easy loss of catalyst active components, environmental pollution, and flammable and explosive hydrogen, which limits its application in industry.
Using a nickel oxide-supported cobalt catalyst, a Co/NiO catalyst with a metal ion Co complex with a NiO support was prepared to prepare a Co/NiO catalyst with a metal Co load of 1.5%, and a catalytic reaction was carried out under high temperature and low pressure conditions, using isopropyl alcohol. Solvent and argon are catalyzed efficiently.
High conversion and high selectivity of furfural to furfurfural alcohol are achieved, with low cost, easy catalyst recovery, optimized reaction conditions, conversion rate of 98.5%, selectivity of 97%, and no hydrogen atmosphere is required.
Smart Images

Figure CN119215899A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomass conversion catalysts, and specifically relates to a nickel oxide-loaded cobalt catalyst and a preparation method and application thereof. Background Art
[0002] A sustainable and stable energy supply is of great significance to the development of human economy and society. Today, the main energy comes from non-renewable resources such as coal, crude oil, and natural gas. However, the exploitation and use of a large number of fossil fuels have brought many problems to human society, such as global warming and environmental pollution. In recent years, in order to solve the problems caused by excessive exploitation and use of fossil energy, people have been committed to finding and developing new green renewable energy. Lignin is a sustainable and stable source of fossil energy, which has the potential to be converted into high-value-added chemicals and replace traditional fossil fuels. The catalysis of biomass-derived platform molecules into value-added chemicals is of great significance to meet the increasing energy demand and reduce CO2 emissions.
[0003] Furfural is a bio-based platform molecule that can be obtained from lignocellulosic materials (such as hemicellulose) by acid hydrolysis. An effective strategy to obtain high value-added products from furfural is to first convert furfural into less reactive intermediates and then into the target products. However, due to the highly functional nature of furfural (i.e., CC, CO and C=O bonds), it is challenging to control the conversion rate and selectivity of furfural to the desired product. In view of this, the commonly used method is selective hydrogenation to produce furfural alcohol, which can be used to produce sand core binders, high temperature resistant phenolic resin binders, plasticizers with excellent cold resistance, synthetic fibers, polyurethane foams, tetrahydrofurfuryl alcohol, etc. required for the foundry industry. In addition, furfural alcohol is also a good solvent for varnishes, pigments, etc., and is an intermediate for the production of pesticides, fragrances and medicines.
[0004] There are two processes for hydrogenating furfural to furfuryl alcohol: liquid phase method and gas phase method. The liquid phase method using Cu-Cr catalyst was industrialized in 1948. The liquid phase method has the characteristics of high temperature, difficult catalyst separation and regeneration, and high equipment requirements. In contrast, the gas phase method has the advantages of low reaction temperature, low pressure, inhibition of deep hydrogenation, and simple catalyst recovery. At present, the catalysts used in the gas phase method are mainly copper-silicon and copper-chromium. Although copper-chromium catalysts have the advantages of high selectivity and high stability, heavy metal chromium will cause pollution to the environment and harm to the human body, which limits the development of copper-chromium catalysts.
[0005] Therefore, the current development direction is mainly focused on the development of chromium-free catalysts. In the existing catalytic system, transition metal catalysts, especially transition noble metal catalysts, such as Ru and Pd, show high catalytic performance in the reaction system of furfural hydrogenation to prepare furfuryl alcohol, but the noble metal catalysts are expensive, and under harsh reaction conditions, the active components of the catalysts are easily lost, resulting in poor catalyst recycling performance, thus limiting its wide application in actual industry; if low-cost non-precious metals such as cobalt, nickel and zinc are used as catalyst active components, it is necessary to maintain high temperature, high pressure and long reaction time at the same time to ensure the complete reaction. The metal waste liquid generated during the reaction will pollute the water body, and the catalyst consumption is large, and the economic benefits are low.
[0006] In addition, for the catalytic preparation of furfuryl alcohol from furfural, the selection of an appropriate hydrogen source is crucial. Currently, there are two main options for the catalytic synthesis of furfuryl alcohol from furfural. In the first option, hydrogen (H2) is used as a hydrogen donor. However, hydrogen under high pressure easily reacts with air and has dangerous properties of being flammable and explosive, requiring special storage, transportation and handling facilities. This limits the widespread application of this option. The second option uses a catalytic hydrogen transfer (CTH) method using formic acid or alcohol as a hydrogen donor. This method is simpler and safer in terms of laboratory facilities and operations. In addition, alcohol solvents have multiple potential roles, acting as both solvents and hydrogen donors, making them attractive. Since furfural is highly unsaturated, the location of the hydrogenation reaction needs to be precisely controlled to improve the selectivity of furfuryl alcohol. At present, this control is usually achieved by adjusting the catalyst, so the selection and structural regulation of the catalyst have become key factors in improving the efficiency of catalytic hydrogenation of furfural to furfuryl alcohol. Different types of catalysts will determine the pathway and product selectivity of the catalytic reaction, so research in this area is crucial.
[0007] Therefore, the development of high catalytic efficiency, low cost, and easy-to-prepare heterogeneous metal catalysts is of great significance for the preparation of furfuryl alcohol from the biomass platform compound furfural. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a nickel oxide-loaded cobalt catalyst and a preparation method and application thereof.
[0009] The present invention is achieved through the following technical solutions:
[0010] A nickel oxide-loaded cobalt catalyst is prepared by adding an auxiliary agent to a complex solution containing metal ions Co and a carrier NiO to prepare a Co / NiO catalyst with a metal Co loading mass fraction of 1.5%, wherein the auxiliary agent is a dispersant and a reducing agent.
[0011] The method for preparing the above-mentioned nickel oxide-supported cobalt catalyst comprises the following steps:
[0012] S1: Mixing a complex solution containing metal ions Co and a dispersant in a solvent and stirring to react to form a colloid, adding NiO to the colloid, and continuing to stir and react to obtain a catalyst precursor;
[0013] S2: adding a reducing agent to the catalyst precursor, stirring the reaction to make the loading ratio of metal Co reach 1.5%, and then filtering and drying to obtain Co / NiO catalyst powder.
[0014] Preferably, in S1, the cobalt acetylacetonate solution and the dispersant polyvinyl pyrrolidone are mixed in deionized water and stirred for reaction for 15 minutes to obtain a colloid, and then NiO is added and stirred for reaction for 10-60 minutes to obtain a catalyst precursor.
[0015] Preferably, in S2, a reducing agent NaBH4 is added to the catalyst precursor to reduce the Co precursor to metallic Co, and the Co content in the cobalt acetylacetonate solution is adjusted so that the loading ratio of metallic Co is 1.5%. After stirring the reaction at room temperature for 2 hours, the solution is filtered.
[0016] Preferably, the filtration in S2 is performed using an aqueous phase filter membrane and deionized water at a temperature of 90° C. for filtration and washing until the filtrate becomes a colorless transparent liquid, and Co / NiO catalyst powder is obtained on the aqueous phase filter membrane. The powder is dried in a vacuum environment at 60° C. to obtain a dry Co / NiO catalyst.
[0017] The use of the above-mentioned nickel oxide-supported cobalt catalyst in the process of preparing furfuryl alcohol from furfural specifically comprises the following steps:
[0018] The Co / NiO catalyst, furfural raw material and isopropanol solvent are placed in a high-pressure reactor, argon gas is introduced, and a high-temperature stirring reaction is carried out. After the reaction is completed, the reactor is cooled to room temperature, and the reactor is depressurized and sampled to obtain furfuryl alcohol.
[0019] Preferably, the Co / NiO catalyst, furfural raw material, and isopropanol solvent are placed in a high-pressure reactor, the gas in the reactor is extracted, 0.1 MPa argon is introduced for purging three times, and 0.1 MPa argon is continuously introduced for 1 min, and then at 120°C, the stirring speed is maintained at 800 rpm, and the reaction is continued for 4 hours. After the reaction is completed, it is cooled to room temperature, and the reactor is vented and sampled and filtered to obtain products such as furfuryl alcohol.
[0020] The beneficial effects of the present invention are:
[0021] (1) The preparation process of the Co / NiO catalyst is simple. The preparation conditions of the catalyst are optimized, and the effects of the Co loading, catalyst mass, reaction temperature, reaction time, etc. on the reaction are adjusted. The high dispersion of transition metal nanoparticles is achieved at the microscopic level, and the reaction obtains the best conversion rate and yield. At the same time, the price and difficulty of obtaining the carrier nickel oxide and metal cobalt are relatively low. The mass fraction of the total metal loading is 1.5%, the loading is small, and the cost is low. In addition, the carrier nickel oxide is magnetic, and it is very easy to separate the product and recover the catalyst, thereby improving the recycling performance of the catalyst.
[0022] (2) The Co / NiO catalyst is used to catalyze the preparation of furfuryl alcohol from furfural, which optimizes the conditions of the catalytic reaction and ensures high catalytic efficiency. In a hydrogen-free atmosphere and at a relatively low reaction temperature, the conversion rate of the reactant furfural reaches 98.5%, and the selectivity of the target product furfuryl alcohol is as high as 97%. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments.
[0024] Figure 1 Transmission electron micrographs of NiO (a, b) and 1.5Co / NiO (c, d) catalysts;
[0025] Figure 2 It is the XRD spectra of NiO and 1.5Co / NiO. DETAILED DESCRIPTION
[0026] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. In addition, the technical features involved in the various embodiments described below can be combined with each other as long as they do not conflict with each other.
[0027] Example 1
[0028] Prepare a Co / NiO catalyst with a metal Co loading of 1.5% by mass: Pour 10 mL of 2.2 mg / mL acetylacetonate cobalt solution into a 250 ml round-bottom flask, and then pour in 150 ml of deionized water and stir evenly. Continue to add 5.4 mg of polyvinyl pyrrolidone with an average molecular weight of 10,000 and stir for 15 minutes. Then add 300 mg of nickel oxide, and after stirring for 15 minutes, add 30 mg of NaBH4 to make the theoretical metal loading ratio 1.5% cobalt. After stirring for 2 hours at room temperature, the above solution was filtered using an aqueous filter membrane with a specification of 50 mm × 0.08 um. Use 2L of deionized water at a temperature of 90°C to filter and wash until the filtrate becomes a colorless and transparent liquid. Then put the catalyst powder on the filter paper into a 60°C vacuum drying oven and dry overnight to obtain a catalyst. Figure 1 As shown in the figure, it can be seen that NiO has a flaky structure, and the introduction of Co does not cause a significant change in the morphology of the NiO carrier. It is dried and kept away from light for future use. Figure 2 It can be seen that NiO mainly presents (111), (200), (211), (311) and (222) crystal planes. The introduction of Co did not cause structural changes in NiO, but no diffraction peak of Co was observed, which is mainly due to the low loading and high dispersion of Co.
[0029] Example 2
[0030] The Co / NiO catalyst with a mass fraction of 1.5% of the metal Co loading prepared in Example 1 is used in the process of preparing furfuryl alcohol from furfural: 60 mg of catalyst, 5 mL of isopropanol solvent, 1 mmol of furfural and a stirring magnet are poured into the polytetrafluoroethylene liner of the high-pressure reactor in sequence. After the reactor is installed, the gas in the reactor is extracted with a high-pressure pump, and then connected to the argon cylinder, and 0.1 MPa of argon is passed through to purge three times. And keep 0.1 MPa to fill with argon, and keep the inflation process for about 1 minute. Finally, the reactor is placed in a high-temperature magnetic stirring oil bath pot with a pre-set temperature of 120°C, the magnetic stirring speed is 800 rpm, and the reaction is carried out for 4 hours. After the 4-hour reaction, the reactor is placed in ice water to cool for 5-10 minutes, the gas in the reactor is released, the reaction liquid in the reactor is sucked with a syringe, and then filtered with a 0.45 nm filter head to obtain the furfuryl alcohol filtrate.
[0031] Example 3
[0032] The relationship between the reaction progress and time of furfural to furfuryl alcohol catalyzed by Co / NiO catalyst with a metal Co loading of 1.5% by mass is tested, as shown in Table 1.
[0033] Table 1 Relationship between reaction progress and time
[0034]
[0035] The results showed that after 4 hours, the reaction had reached a conversion rate of 98.5%, demonstrating the extremely high efficiency of the catalyst. After 6 hours, the conversion rate reached 99.2%.
[0036] Example 4
[0037] The effect of the cobalt content in the tested catalysts on the catalytic performance is shown in Table 2.
[0038] Table 2 Effect of cobalt content in catalyst on catalytic performance
[0039]
[0040] The results show that in the catalyst of the present invention, the loading amount of Co metal greatly improves the conversion rate of furfural, and when the loading amount of Co metal is 1.5%, the best catalytic effect is achieved. Excessive loading of Co will lead to a decrease in the conversion rate of the catalyst, so a Co loading amount of 1.5% is selected as the most suitable catalyst loading amount for the reaction.
[0041] Example 5
[0042] The effect of catalyst dosage on catalytic performance was tested, as shown in Table 3.
[0043] Table 3 Effect of catalyst dosage on catalytic performance
[0044]
[0045] The results show that after 4 hours of reaction, the conversion rate of the reactants reached 98.5% only when the catalyst mass was greater than or equal to 60 mg. There was basically no difference in the reaction results when the catalyst mass was 60 mg and 80 mg. Therefore, 60 mg was selected as the most suitable catalyst mass for the reaction.
[0046] Example 6
[0047] The catalytic effects of the tested catalysts on different aldehyde-containing substrates are shown in Table 4.
[0048] Table 4 Catalytic effect of catalysts on different aldehyde-containing substrates
[0049]
[0050] The results showed that the catalyst could selectively catalyze hydrogen transfer on a series of unsaturated aldehyde substrates to prepare corresponding alcohol compounds.
[0051] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all details in detail, nor do they limit the invention to only the specific embodiments described. Obviously, many modifications and changes can be made according to the content of this specification.
Claims
1. A nickel oxide-supported cobalt catalyst, characterized in that: A Co / NiO catalyst with a metal Co loading of 1.5% by mass is prepared by adding an auxiliary agent to a complex solution containing metal ions Co and a carrier NiO, wherein the auxiliary agent is a dispersant and a reducing agent.
2. The method for preparing a nickel oxide-supported cobalt catalyst according to claim 1, characterized in that: The following steps are involved: S1: Mixing a complex solution containing metal ions Co and a dispersant in a solvent and stirring to react to form a colloid, adding NiO to the colloid, and continuing to stir and react to obtain a catalyst precursor; S2: adding a reducing agent to the catalyst precursor, stirring the reaction to make the loading ratio of metal Co reach 1.5%, and then filtering and drying to obtain Co / NiO catalyst powder.
3. The method for preparing a nickel oxide-supported cobalt catalyst according to claim 2, characterized in that: In S1, the cobalt acetylacetonate solution and the dispersant polyvinyl pyrrolidone are mixed in deionized water and stirred for reaction for 15 minutes to obtain a colloid, and then NiO is added and stirred for reaction for 10-60 minutes to obtain a catalyst precursor.
4. The method for preparing a nickel oxide-supported cobalt catalyst according to claim 2, characterized in that: In S2, a reducing agent, NaBH4, is added to the catalyst precursor to reduce the Co precursor to metallic Co. The Co content in the cobalt acetylacetonate solution is adjusted so that the loading ratio of metallic Co is 1.5%. After stirring the reaction at room temperature for 2 hours, the solution is filtered.
5. The method for preparing the nickel oxide-supported cobalt catalyst according to claim 4, characterized in that: In the S2, the filtration is performed by using an aqueous phase filter membrane and deionized water at a temperature of 90° C. for filtration and washing until the filtrate becomes a colorless transparent liquid, and a Co / NiO catalyst powder is obtained on the aqueous phase filter membrane. The powder is dried in a vacuum environment at 60° C. to obtain a dry Co / NiO catalyst.
6. The use of the catalyst of nickel oxide loaded with cobalt in the process of preparing furfuryl alcohol from furfural according to claim 1, characterized in that: The specific steps include: The Co / NiO catalyst, furfural raw material and isopropanol solvent are placed in a high-pressure reactor, argon gas is introduced, and a high-temperature stirring reaction is carried out. After the reaction is completed, the reactor is cooled to room temperature, and the reactor is depressurized and sampled to obtain furfuryl alcohol.
7. The use of the cobalt-supported nickel oxide catalyst in the process for preparing furfuryl alcohol from furfural according to claim 6, characterized in that: Co / NiO catalyst, furfural raw material and isopropanol solvent were placed in a high-pressure reactor, the gas in the reactor was extracted, 0.1 MPa argon was introduced for purging three times, and 0.1 MPa argon was continuously introduced for 1 min. Then, at 120°C, the stirring speed was maintained at 800 rpm, and the reaction was continued for 4 hours. After the reaction was completed, it was cooled to room temperature. After the reactor was vented, samples were taken and filtered to obtain furfuryl alcohol and other products.
Citation Information
Patent Citations
Catalyst used for increasing oil shale oil yield, and preparation method and applications thereof
CN109985627A
Nickel sulfide / nickel oxide electrode and preparation method and application thereof
CN117070989A
Catalyst compositions for reforming hydrocarbons
GB1361882A
Improved process for preparation of improved supported catalyst useful for oxidative conversion of methane, natural gas and biogas to synthetic gas
IN189145B
Systems and methods for reforming a heavy aromatic stream
US20230122414A1